Extremely frequent bee visits increase pollen deposition but reduce drupelet set in raspberry - Sáez, Agustín (2014)
1. Production of many flowering crops often benefits from elevated pollinator diversity and abundance. Nevertheless, the opposite relationship may arise if bees impair fruit or seed production and/or quality by damaging flowers during visitation, despite transferring pollen. 2. We assessed pollination and drupelet set (i.e. the number of drupelets per fruit) in 16 raspberry Rubus idaeus fields along a gradient of bee abundance in north-west Patagonia, Argentina. Using pollen supplementation, we also tested whether drupelet set was pollen limited in a subset of six fields. 3. Managed Apis mellifera and the invasive bumblebee Bombus terrestris accounted for 50% and 45% of all bee visits, respectively, to raspberry flowers. Pollen loads on stigmas increased with visit frequency of all bees combined and particularly with visitation by A. mellifera, but not by B. terrestris. Drupelet set was not pollen limited along the gradient of bee abundance. 4. Instead, drupelet set decreased with the proportion of damaged styles, which varied more strongly with the frequency of visits by B. terrestris than by A. mellifera. In fields with the highest bee frequency of visits ( 300 visits flower1 day1 ), 80% of styles were damaged in flowers and these developed into fruits with 30% fewer drupelets compared to flowers in fields with the lowest bee visitation rates ( 4 visits flower1 day1 ). 5. Synthesis and applications. Extreme bee visitation, particularly by Bombus terrestris, damaged the styles of raspberry flowers, precluding ovule fertilization by deposited pollen and limiting crop production by reducing drupelet set. Only a few bee visits are required to maximize fruit production in raspberry plants, therefore, pollinator management in north-west Patagonia should focus principally on reducing the abundance of the invasive bumblebee B. terrestris and secondarily controlling the number of honeybee hives in nearby cultivated fields. Although mainstream pollinator management relies on the assumption that more visits enhance fruit set, high bee visitation rates can be detrimental for fruit development and, consequently, for crop yield.